2019
DOI: 10.1177/1074248419858116
|View full text |Cite
|
Sign up to set email alerts
|

Oral Anticoagulants in Patients With Atrial Fibrillation and End-Stage Renal Disease

Abstract: The role of oral anticoagulants (OAC) in atrial fibrillation (AF) is well established. However, none of the randomized controlled trials included patients with end-stage renal disease (ESRD) leaving a lack of evidence in this large, challenging and unique patient group. Patients on hemodialysis (HD) with AF have additional risk factors for stroke due to vascular comorbidities, HD treatment, age, and diabetes. Conversely, they are also at increased risk of major bleeding due to uremic platelet impairment. Antic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…First, the effect of dabigatran might be reduced in hemodialysis patients as 50–60% of dabigatran is dialyzable ( 1 ). Second, clinical use of dabigatran shortly after its approval in the United States showed high rates of major and non-major bleeding in patients with hemodialysis ( 37 ), this might result from the high renal clearance rate of dabigatran (~80%) ( 38 ) and accumulation of dabigatran in patients with severe renal impairment (a 6.3-fold higher AUC in these patients) ( 39 ). Therefore, rivaroxaban, apixaban, and edoxaban (but not dabigatran) are approved in Europe for use in patients with severe CKD, with a reduced dose regimen.…”
Section: Discussionmentioning
confidence: 99%
“…First, the effect of dabigatran might be reduced in hemodialysis patients as 50–60% of dabigatran is dialyzable ( 1 ). Second, clinical use of dabigatran shortly after its approval in the United States showed high rates of major and non-major bleeding in patients with hemodialysis ( 37 ), this might result from the high renal clearance rate of dabigatran (~80%) ( 38 ) and accumulation of dabigatran in patients with severe renal impairment (a 6.3-fold higher AUC in these patients) ( 39 ). Therefore, rivaroxaban, apixaban, and edoxaban (but not dabigatran) are approved in Europe for use in patients with severe CKD, with a reduced dose regimen.…”
Section: Discussionmentioning
confidence: 99%
“…19 20 Unfortunately, evidence from clinical trials for the use of DOACs is lacking in AF patients with CKD or end-stage renal disease, and recommendations are conflicting. [21][22][23][24] A recent meta-analysis of 16 observation studies evaluated the clinical benefit of DOACs for AF patients on long-term dialysis and concluded that anticoagulation therapy with DOACs in this patient population was not associated with a decreased risk of thrombosis and embolism-related diseases. Further, higher bleeding risk was associated with the use of warfarin, dabigatran and rivaroxaban compared with the use of apixaban and no anticoagulant.…”
Section: Discussionmentioning
confidence: 99%
“…They are also at increased risk of serious bleeding from uremic platelet dysfunction. Anticoagulation treatment increases the risk of bleeding in patients with end-stage renal disease and HD-treated patients up to 10 times compared to warfarin-treated patients with normal renal parameters [37]. Arnson et al [38] conducted an analysis assessing the safety of OAC use in patients with chronic kidney disease (CKD).…”
Section: Limitations Of Anticoagulation In Patients At High Risk Of Thromboembolismmentioning
confidence: 99%